Iron Deficiency Anemia among In-School Adolescent Girls in Rural Area of Bahir Dar City Administration, North West Ethiopia - Getachew Mengistu; Muluken Azage; Hordofa Gutema (Anemia)
Background. Anemia is a major public health problem worldwide. Adolescent girls are the most vulnerable group of population due to different reasons. The aim of this study was to assess the prevalence of anemia and associated factors among school adolescent girls in rural towns of Bahir Dar City Administration, North West Ethiopia. Methods. A cross-sectional study was conducted from March 5 to April 15, 2017, on 443 randomly selected school adolescent girls. Data were collected using pretested structured questionnaire and anthropometric measurements. Blood sample was also collected to assess the hemoglobin (Hgb) value of study participants. SPSS version 20 was used to analyze data. Descriptive statistics were used to describe data. Bivariate and multivariable logistic regression models were used to identify the associated factors with the outcome variable. Crude and adjusted odds ratios with 95% confidence interval (CI) were calculated to identify the variables significantly associated with the outcome variable. Result. The prevalence of anemia was 11.1%. Household family size [AOR=3.2, 95%CI (1.29-7.89)], average household monthly income <500 ETB [AOR=10; 95%CI (2.49-41.26)], 501-1000 ETB [AOR=6, 95%CI (2.54-14.33)], history of intestinal parasitic infection [AOR=2.7; 95% CI (1.19-6.21)], duration of menstruation flow [AOR=2.4; 95%CI (1.08- 5.44)], and BMI for age [AOR-3.2; 95% CI (1.43-7.05)] were the predictors of anemia. Conclusion and Recommendation. Anemia was a mild public health problem among school adolescent girls in the study area. Household monthly income, family size, intestinal parasite infections, duration of menstruation, and BMI for age are predictors of anemia. Thus, intervention strategies should focus on prevention and early treatment of intestinal parasite, nutritional education, screening, and iron supplementation programs to prevent anemia among school adolescent girls.